PENGARUH PROGRAM KONSERVASI MANGROVE TERHADAP KUALITAS LINGKUNGAN DI DESTINASI EKOWISATA KABUPATEN BINTAN - Sihite, Hetty Yulianti (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
This study aims to analyse the influence of mangrove conservation programs on environmental quality within the ecotourism destinations of Bintan Regency. Given the rapid growth of tourism, maintaining ecological balance has become critical. Utilising a quantitative causal associative approach, the research involved a sample of 76 respondents from a total population of 304 visitors and stakeholders. Data were collected through Likert-scale questionnaires and processed using simple linear regression. The findings demonstrate a significant positive effect, as indicated by the regression equation Y = 25.763 + 0.299X. Statistical analysis yielded a t-value of 4.149, exceeding the t-table threshold of 1.990 (p < 0.05), which confirms that conservation initiatives effectively enhance habitat quality. Furthermore, the coefficient of determination (R²) was 0.189, indicating that conservation efforts explain 18.9% of the improvement in environmental quality, with other external factors accounting for the remainder. The study concludes that integrating reforestation with ecotourism education is vital for sustaining Bintan's coastal ecosystem.